PENGARUH IKLIM ORGANISASI TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Fajri Nur Hidayat (Jurnal Ekonomi dan Bisnis Airlangga, 2019)
Introduction: Division of research and development to produce performance played a central role in the form of technological innovation cultivation of sugar cane and innovation performance of the global industrial competition. Required organizational climate that support performance improvement and business development research staff. Mutual support and encouragement in every settlement between management and employees work will provide a comfortable atmosphere in the performance of employees. High motivation for staff to be able to grow a maximum potential and competence of employees wants to work hard to realize the company's strategic objectives.Methods: To examine these issues, a questionnaire distributed to 35 staff in research and development of PTPNXI (Persero). The collected data were analyzed using SPSS analysis techniques. Results: The results showed that the significant effect of organizational climate on employee performance. Thus a good organizational climate will cause the employee improve performance. Good organizational climate and always oriented employment relationship in shaping the behavior of employees can motivate employees that will result in optimal performance of employees at work.Conclusion and suggestion: Managerial advice to do is apply organizational climate in PTPN XI (Persero) staff research and development efforts should be made clear again that the work climate that is able to adapt to the situation and condition of the employee. The next suggestion, leaders continue to increase employee motivation by not ignoring the rights and interests of employees as provide promotional opportunities, improved employee supervision system, increase confidence in the leadership, and maintain harmonious relationships between colleagues.